Towards an anthropology of the bureaucracy - Varela Barrios, Edgar (Cuadernos de Administración, 2009)
This article realises an analysis of the notion of bureaucracy from an anthropologic perspective, departing from the founding Weber’s paradigm up to postbureaucratic theories and their correlations with political organizations, transnational companies, as well as with the organisms for cooperation and international help. In the same way, relations are established between the notion of bureaucracy seen from Political Science and the management theories, in the frame of public management and the transnationalisation of public policies